Poster 165: Psychosocial Factors Play a Greater Role in Preoperative Symptoms for Patients with Atraumatic Shoulder Instability: Data from the Moon-Shoulder Instability Group. Issue 7 (30th July 2022) - Jacobs, Cale; Lemaster, Nicole; Ortiz, Shannon; Magnuson, Justin; Hettrich, Carolyn; Nichols, Michael
Objectives: Previous studies have demonstrated altered brain activation patterns on functional MRI for those with shoulder instability suggesting a potential link between recurrent instability, depression, and emotional wellbeing. It is unknown whether this potential link would differ between those with traumatic vs. atraumatic instability. The purpose of this study was to determine whether psychosocial factors and/or comorbid depression play a greater role in preoperative symptoms for patients with atraumatic or traumatic mechanisms of shoulder instability. We hypothesized that when controlling age, sex, and direction of instability, psychosocial factors and comorbid depression would be more predictive of shoulder-related pain and symptoms for patients with atraumatic instability than patients with traumatic instability. Methods: As part of the IRB-approved Multicenter Orthopaedic Outcomes Network (MOON) Shoulder Instability cohort, 1553 patients provided informed consent and completed pre- and intraoperative data collection. Patients were categorized based on self-reports of whether the mechanism of shoulder instability was traumatic (n=1267) or atraumatic (n=286). Multivariable linear regressions were performed to determine whether psychological factors (VR12, Mental Component Score (MCS), Depression Diagnosis, PAS-22) were predictive of preop ASES and WOSI score in the atraumatic group, controlling for age, sex, and the direction of instability. The same model was repeated for the traumatic instability group, and the model fit was compared between groups using the methods described by Cohen, Cohen, and West with p < 0.05 considered statistically significant. Results: Sex and Mental Component Scores (MCS) were significantly predictive of preop ASES and WOSI scores for the group with atraumatic instability (ASES r 2 =0.15, p<0.001; WOSI r 2 =0.17 p<0.001). The same model performed significantly worse for both ASES and WOSI scores in the group with traumatic instability (ASES r 2 =0.06, WOSI r 2 =0.07, p<0.05 for both ASES and WOSI). Conclusions: Preoperative psychosocial factors were found to be more predictive of shoulder-related pain and symptoms for patients with atraumatic instability. Across multiple orthopedic conditions, depression and emotional wellbeing have been associated with worse preoperative symptoms and inferior postoperative patient-reported outcomes. As opposed to medically optimizing patients prior to surgery, the current findings identify a subset of shoulder instability patients that may need to be psychologically optimized either prior to surgery or early in the postoperative period to potentially improve postoperative outcomes.